Family Ellobiidae (Gastropoda: Archaeopulmonata) in the Peruvian coast - Paredes, Carlos (2005)
We report 8 species of Ellobiidae from the Peruvian coast, which belong to the subfamilies Ellobiinae: Ellobium stagnale (Orbigny, 1835) and Sarnia frumentum Petit, 1842; Melampodinae: Melampus carolianus (Lesson, 1842), Melampus olivaceus Carpenter, 18574 and Detracia graminea Morrison, 1846; and Pedipedinae: Marinula acuta (Orbigny, 1835), Marinula concinna (C.B Adams, 1852) and Marinula pepita King, 1831. Six species live associated to the mangrove of the department of Tumbes, and two in boulder beaches in the limits of the Peruvian Province. Four tropical species are registered for the first time in the Peruvian Sea: A. stagnale, M. olivaceus, D. graminea and M. acuta.